Size-selective glomerular filtration as a hallmark of premature kidney ageing in nondiabetic individuals - Laucyte-Cibulskiene, Agne ; 0000-0003-4020-1467; Nilsson, Christopher ; 0000-0001-8399-8854; Jujic, Amra ; 0000-0002-9506-0158; Holm, Hannes; Christensson, Anders (Clinical Kidney Journal, 2025)
Background During the last decade, evidence has emerged on selective glomerular hypofiltration syndromes (SGHS), defined by selectively reduced filtration of middle-sized molecules irrespective of kidney function and resulting in a low ratio between cystatin C- and creatinine-based estimated glomerular filtration rates (eGFRcys/eGFRcr). We aimed to examine whether SGHS is a hallmark of premature kidney ageing manifested by accumulation of advanced glycation end-products (AGEs) and endothelial dysfunction in a population free from chronic kidney disease and diabetes. Methods A total of 3804 participants of The Malmö Offspring Study (MOS) underwent AGE (skin autofluorescence acquired), eGFRcys and eGFRcr measurements. AGEs ≥1.6 were categorized as high, and AGEs <1.6 as normal. Reactive hyperemia index (RHI) was available in 2204 participants; RHI <1.67 indicated endothelial dysfunction (ED), and RHI ≥1.67 normal endothelial function (EF). Combining AGEs and RHI, four groups were compared: (group 1) AGEs <1.6 and EF, (group 2) AGEs <1.6 and ED, (group 3) AGEs ≥1.6 and EF, and (group 4) AGEs ≥1.6 and ED. Results Lower eGFRcys/eGFRcr ratio was associated with an increase in AGEs in men and women. After adjusting for cardiovascular factors, lower eGFRcys/eGFRcr ratio was associated with AGE accumulation in men older than 30 years. The 'AGEs ≥1.6 and ED' and 'AGEs ≥1.6 and EF' groups showed the highest prevalence of eGFRcys/eGFRcr under 0.9 (in men, 22% vs 19.7%, in women 19.5% vs 16%, respectively). Conclusions Accumulation of AGEs resulting from SGHS leads to age dependent changes in glomerular basement membrane and increased selectivity for middle-sized molecules. Presence of these findings in younger individuals supports the hypothesis that SGHS is a model of early kidney ageing, occurring before decline in kidney function.
Publisher Copyright: © 2025 The Author(s). Published by Oxford University Press on behalf of the ERA.
Keywords: advanced glycation end products; cystatin C; estimated glomerular filtration rate; kidney ageing; size-selective kidney filtration